Can Spiritual Ecograms be Utilized in Mental Health Services to Promote Culturally Appropriate Family and Couples Therapy with Indigenous People? - Elliott, Nicole (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2012)
Research addressing the potential utilization of spiritual ecograms with Indigenous families and children, specified by experienced professional in the field of Native-American psychology, was critiqued and reviewed in order to attend to its influence and applicability regarding the literature of Indigenous family therapy, and how it could be beneficial in therapy with Indigenous families. The literature review presents an effective tool, providing an in-depth exploration of spiritual strengths of the family and or children that incorporates spirituality into techniques commonly used in family therapy practice. Study results (Limb & Hodge, 2011) show that this tool is consistent with Native-American culture (Brucker & Perry, 1998; Green, 2010; Paniagua, 2005; Trujillo, 2000) and highlights many beneficial qualities for its utilization in practice. Limitations and recommendations for future research are also discussed.